Digital Media Literacy Strategy to Address Character Assassination of the West Java Governor Among University Students in Bandung - Anggita Lestari; Nugraha Sugiarta; Arya Muhamad Zaelani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to examine the role of digital media literacy in addressing the phenomenon of character assassination against the Governor of West Java among students in Bandung. In today’s digital era, the spread of inaccurate or harmful information can quickly circulate through social media and other digital platforms, potentially damaging an individual’s reputation. Students, as an active and critical age group in using digital media, are at high risk of becoming both targets and spreaders of detrimental information. This study employs a qualitative approach, using in-depth interviews and focus group discussions (FGDs) with students from several universities in Bandung to understand their perspectives on digital media literacy and their responses to information related to character assassination. The results indicate that, while students possess a basic understanding of digital media, many still struggle to identify and counter the spread of inaccurate information, particularly regarding political issues. Furthermore, students tend to underutilize skills in information verification and understanding the negative impacts of disseminating harmful information. Therefore, this study underscores the importance of strengthening digital media literacy to enhance students’ critical abilities in addressing character assassination, with a focus on skills such as source verification, contextual analysis, and ethical information dissemination. This study recommends that digital media literacy be further incorporated into higher education curricula to better prepare students to become responsible and discerning media users in the digital age.